Research methodology: A critical analysis of contemporary Muslim scholarship in Southeast Asia - Yousif, Ahmad (2012)

(untitled)
In Southeast Asia, as well as other parts of the Muslim world, academic institutions often ignore the importance of research methodology as an instrument for determining solutions to particular problems. This is especially evident in the field of Islamic Studies. Generally speaking, many institutions of higher learning in Southeast Asia conduct research in the Islamic disciplines using traditional approaches and techniques. Although such approaches do have some merits, they have a number of disadvantages. Consequently, many scholars and students in the Islamic disciplines often face difficulties and challenges when conducting research due to the use of methodologies which lack innovativeness, efficiency and over-all effectiveness. In an effort to reduce some of the deficiencies of the traditional approach to research, some scholars prefer to completely reject such methods in favor of western research methodologies. This paper will examine the importance of research techniques within an Islamic framework of knowledge, the merits of both traditional and western research methodological techniques, as well as propose various recommendations for overcoming the limitations of the two approaches. It is hoped that these efforts will lead towards the development of a new model which will be able to combine the strengths of both techniques, while at the same time minimizing their weaknesses.